Chapter О культурных предпосылках 'итальянского' правового дискурса Сергея Ивановича Зарудного - Goletiani, Liana (Biblioteca di Studi Slavistici, 2019)
The paper is about Sergej Ivanovič Zarudnyj, a central figure in Tsar Alexander II's "great reforms". Descended from the family of a Cossack staršyna from Sloboda Ukraine, Zarudnyj had a brillant career in the imperial capital as a engaged reformer of Russia's backwards legal system. His cultural origins, his family's history, and his education at Kharkiv University deeply affected his translation work and legal discourse; in both of these spheres, he aimed to introduce and popularize the products of Italian legal culture in the Russian Empire.